War and Peace: The Peculiarities of Ukrainian-Russian Scientific Cooperation Dynamics Against the Background of Russian Military Aggression in Ukraine, in 2014-2016 - Nazarovets, S.A. (Science and Innovation, 2024)
The paper presents the results of bibliometric analysis of publications co-written by authors affiliated with Ukrainian and Russian institutions in 2007-2016, based on Scopus data. The survey results have showed that Ukrainian and Russian researchers continue carrying out joint research in major international projectsю However, a decrease in the number of works published by Ukrainian and Russian research institutions in 2016 has testified to an adverse impact of Russia’s military aggression on cooperation in the field of science. The findings are important for preparing the science development programs in Ukraine.